PENGARUH MOTIVASI, KECERDASAN EMOSIONAL, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA MELALUI KEPUASAN KERJA DOSEN PERGURUAN TINGGI SWASTA DI BANJARMASIN - MAHFUZIL ANWAR (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,Motivation is formed on indicators of physiological needs, safetyneeds, social needs, esteem needs and self actualization needs. The studyresult shows the dominant indicator which formed the motivation variable isthe esteem needs, from the statement item of recognition needs in theorganization and in the community. Emotional intelligence is formed onindicators of self awareness, self control,self motivation, empathy, and socialskills. The study result shows the self control statements of having aresponsibility sense and willing to accept criticism, are able to formemotional intelligence variable. Tranformational leadership is formed onfour incicat statement item of supporting group work. Tranformationalleadership is formed on four incicators which are charismatic, having oninfluence, having a vision, and transforming subordinates’mind.The studyresult show the indicator of having a vision has the highest weight value onthe statementitem of having a clear vision is able to explain thetransformational leadership. Job satisfaction is formed on indicators ofpresence frequency, liking the job, liking the environment, liking thesupervisor, participation frequency and retention level. The study resultshows the indicator of retention level has the highest weight value on thestatement item of feeling satisfied for working in the institution. It means thelecturers’ retention is dominantly able to explain the job satisfaction thanother indicators. Job performance is formed on quality, quantity, tumelienss,cost effectiveness, needs for supervision, and interpersonal impact. The studyresult shows the interpersonal impact indocatorhas the highest weight valueamong the other, on the statement item of having pride. It meansthelecturers’ interpersonal impact is dominantly able ti explain the jobperformance the the quality, quantity, timeliness, cost effectiveness, andneeds for supervisions.